2021
DOI: 10.3390/ijms22041926
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative and Quantitative Comparison of Plasma Exosomes from Neonates and Adults

Abstract: Exosomes are extracellular vesicles that contain nucleic acids, lipids and metabolites, and play a critical role in health and disease as mediators of intercellular communication. The majority of extracellular vesicles in the blood are platelet-derived. Compared to adults, neonatal platelets are hyporeactive and show impaired granule release, associated with defects in Soluble N-ethylmaleimide-sensitive fusion Attachment protein REceptor (SNARE) proteins. Since these proteins participate in biogenesis of exoso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 67 publications
(112 reference statements)
1
16
0
Order By: Relevance
“…126 A recent paper showed that neonatal EVs from umbilical cord blood are different in size, concentration and in their protein content from adult EVs, with an increased expression of prothrombotic proteins and a lower expression of immunoglobulins. 127 This supports previous work from our group examining size and concentration of neonatal EVs and how this alters in the first 3 days in premature infants. 128 In addition to EVs, degranulation is associated with the release of a range of proteins termed the platelet releasate.…”
Section: Platelet-derived Evs and The Platelet Proteome/ Secretome In Sepsissupporting
confidence: 89%
“…126 A recent paper showed that neonatal EVs from umbilical cord blood are different in size, concentration and in their protein content from adult EVs, with an increased expression of prothrombotic proteins and a lower expression of immunoglobulins. 127 This supports previous work from our group examining size and concentration of neonatal EVs and how this alters in the first 3 days in premature infants. 128 In addition to EVs, degranulation is associated with the release of a range of proteins termed the platelet releasate.…”
Section: Platelet-derived Evs and The Platelet Proteome/ Secretome In Sepsissupporting
confidence: 89%
“…Studies have revealed that the main therapeutic effect of platelets during bleeding is dependent on the effect of platelet-derived extracellular vesicles [ 28 ]. Neonatal plasma exosomes can be enriched in a large number of proteins involved in platelet function and primary hemostasis, such as platelet activation and signaling proteins, integrins α IIb and β 3, platelet chemotactic protein (PF4), filaggrin-A, and ligand receptor (CD36) [ 29 ]. The use of platelet exosomes shows the advantage of the hemostatic effect over fresh platelets [ 30 ].…”
Section: Mechanisms Of Msc-derived Nanovesicles In Wound Healingmentioning
confidence: 99%
“…[20][21][22] Among them, exosomes (Exo) are a group of extracellular vesicles with diameters ranging from 30 to 160 nm. 23,24 Exo are thought to functionally mediate cell-to-cell communication by transferring diverse bioactive substances such as proteins, mRNA, and small non-coding RNAs. 25,26 Previous studies demonstrated that MSC-Exo could mimic the capabilities of MSCs to enhance recovery in animal models of liver injury and liver regeneration.…”
Section: Introductionmentioning
confidence: 99%